Effect of AKD concentration as crosslinker in PVA/ZnO film for food packaging application - Khan, Sulaiman; Norshahirah, Roslan; Nur Fatini Ilyana, Mohamat Johari; Farah Hanani, Zulkifli (American Institute of Physics, 2025)
The aim of this study is to analyze the incorporation of alkyl ketene dimer (AKD), a non-toxic and environmentally friendly chemical, in combination with polyvinyl alcohol (PVA) and zinc oxide (ZnO) nanoparticles. The PVA/ZnO/AKD films were synthesized at varied concentrations of AKD (1 - 3 wt.%) and fabricated by using solution casting method. The prepared films were analyzed using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The presence of AKD in the PVA/ZnO films was confirmed by strong XRD peaks at 32.08°, 34.7°, and 36.8°. Compared with PVA/AKD, a new FTIR band at 1710 cm-1 was observed for the PVA/ZnO/AKD films, and its intensity increased with increasing AKD content. Moreover, the addition of AKD altered the morphology of the PVA/ZnO matrix. Higher magnification images revealed the accumulation of flake-like structures on the rough surface substrate (Figure 3d-e). The effects of varying AKD concentration on water resistance, water vapor transmission rate (WVTR), UV barrier properties, and soil burial degradation were also examined. The combination of PVA, AKD, and ZnO nanoparticles resulted in enhanced properties, making these films highly promising for food packaging applications.